Vitamin D fortification and seasonality of birth in type 1 diabetic cases: D-tect study. (27th October 2015) - Jacobsen, R.; Moldovan, M.; Vaag, A. A.; Hypponen, E.; Heitmann, B. L.
Abstract : Fortification of margarine with vitamin D was mandatory in Denmark during 1961–1985. The aim of the study was to assess whether gestational and early infancy exposure to margarine fortification was associated with seasonality of birth in Danish type 1 diabetes (T1D) patients. The risks of T1D in Danes born during various exposure periods around margarine fortification termination in 1985 were analyzed. As expected, the T1D hazards in males unexposed to margarine fortification and born in spring were higher than in males born in autumn: relevant hazard ratios (95% confidence intervals) in various exposure groups ranged from 1.74 (1.112/2.708) to 37.43 (1.804/776.558). There were no indications of seasonality of birth in males exposed to fortification, nor in both exposed and unexposed females. The study suggests that early life exposure to low-dose vitamin D from fortified food eliminates seasonality of birth in T1D male patients. Further studies are required to investigate the identified gender differences.